Experimental Comparison between Hydrokinetic Turbines: Darrieus vs. Gorlov - Rodolfo Espina-Valdés; Ahmed Gharib-Yosry; Roberta Ferraiuolo; Aitor Fernández-Jiménez; Victor Manuel Fernández-Pacheco (Environmental Sciences Proceedings, 2022)
In this research, the influence of blade geometry on the power stage characterization of cross-flow hydrokinetic turbines and vertical axis under conditions of low current velocity (<1 m/s) has been studied. To carry out the characterization of the power stage, two turbines have been used. The first has three straight blades and corresponds to a SC-Darrieus-type rotor, while the second has three corresponding helical blades with a Gorlov-type rotor. The experimental study has been performed by using a hydrodynamic tunnel and a high precision torque meter with an electric brake, which allows one to obtain the necessary mechanical parameters (torque, rotation speed) for the characterization of the power stage. Analyzing the data obtained from the results of the experimental study, it is determined that, for the same water speed, the Gorlov rotor obtains greater mechanical power than the Darrieus type. In all cases, power coefficient values greater than 1 have been obtained, thus verifying the influence of the blocking phenomenon on the performance of the turbines when they are in confined flow conditions. In turn, the TSR values obtained indicate that these turbines will work mainly by lift since they are higher than unity.